A Kite for Moon - Yolen, Jane; Stemple, Heidi E. Y.; Phelan, Matt (Grand Rapids, Michigan : Zonderkidz, 2019)
A young boy, seeing that Moon is lonely, sends up a kite to cheer her then, after growing up and learning many things, he becomes the first human to visit her. Dedicated to Neil Armstrong and written in recognition of the fiftieth anniversary of the first U.S. moon landing.
New Kids Book 2023 Fall.
Keywords: Space flight to the moon -- Fiction; Moon -- Fiction